China Watershed Management Project : Development of a Monitoring and Evaluation System, Final Report - World Bank (Washington, DC, 2012)
The objective of this assignment was to develop a Monitoring and Evaluation (M&E) system for watershed management in the Loess Plateau area. The M&E system for the China Watershed Management Project (CWMP) has been developed on the base of the M&E system that has been implemented during the previous two phases of the World Bank Loess Plateau Project. The final report presents the main outcomes of this process. The major findings of the M&E systems review are summarized in the following chapter two. The steps of developing and agreeing the M&E framework are presented in chapter three. Chapter four will describe the specific features of and challenges for watershed M&E before chapter five goes into a detailed presentation of the M&E framework. The M&E framework is most significant outcome of this assignment because it brings together all the agreements and considerations around institutional and methodological issues of M&E. The key parameters for M&E are defined in the framework, but they are further specified into operational steps in the M&E guidelines which are prepared as a separate document.